Injectable self-hardened synthetic bone cement (osteopaste) as a filler for bone defects: A histological result from experimental study in New Zealand white rabbits’ tibia - Che Seman, Che Nor Zarida (2019)
Calcium phosphate cements have become a subject of interest in biomedical material researchers to promote healing of bone fracture or in reconstructed bone defects because of their excellent biocompatibility and bioactivity1. So far, there is no locally product of injectable calcium phosphate cement in Malaysia. Therefore, injectable Osteopaste has been designed to conduct pre-clinical evaluations (in vivo) on critical size bone defects (CSD) of New Zealand White rabbits. The implantation of injectable Osteopaste was compared with currently available commercialized bone graft namely Jectos (calcium phosphate) and MIIG® – X3 (calcium sulphate). This injectable Osteopaste is hoped to be used as an alternative bone graft substitute to promote new bone formation and bridge the critical size bone defects.